What assistance is needed? : assessment for literacy learning difficulties in NZ schools : a thesis presented in partial fulfilment of the requirements for the degree of Master of Educational Psychology at Massey University, Albany, New Zealand - Neville, Angela (Massey University, 2017)
At the present time, contemporary information regarding effective assessment and remediation practices for children with literacy learning difficulties in New Zealand/Aotearoa schools is scarce. The aim of the present study was to fill that gap in our understanding by carrying out a survey of current practices and comparing these with the research literature on best practice in assessment and remediation. To address the research questions, an online survey was developed and emailed to all schools in New Zealand/Aotearoa. There were 208 responses from a wide range of schools across the country and from a number of specialist teachers and school leaders. In addition to the online survey, interviews were carried out with 13 of the respondents, representing both teachers and specialist teachers. The results indicated a wide diversity of assessment and remediation practices in schools for students with literacy learning difficulties. A possible explanation for this is that assessment and remediation methods are often tied to theoretical views of the literacy process. At the current time in New Zealand/Aotearoa there are varied theoretical perspectives that seem to account for that diversity, in particular, the difference between whole language and phonological theories and their implications for assessment and remediation. The results from this study indicated that teachers and specialists were focusing mainly on proximal factors in assessment and were teaching to those factors. They paid less attention to the assessment of distal factors which is more of a focus among psychologists. This study provides the basis for further discussion into how best to identify and remediate students with literacy learning difficulties in New Zealand/Aotearoa.
Keywords: Educational tests and measurements; Language arts; Reading disability; Learning disabilities; New Zealand; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education